2016
DOI: 10.1186/s40644-016-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

A study on the value of computer-assisted assessment for SPECT/CT-scans in sentinel lymph node diagnostics of penile cancer as well as clinical reliability and morbidity of this procedure

Abstract: BackgroundBecause of the increasing importance of computer-assisted post processing of image data in modern medical diagnostic we studied the value of an algorithm for assessment of single photon emission computed tomography/computed tomography (SPECT/CT)-data, which has been used for the first time for lymph node staging in penile cancer with non-palpable inguinal lymph nodes. In the guidelines of the relevant international expert societies, sentinel lymph node-biopsy (SLNB) is recommended as a diagnostic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Hip and knee replacement is a procedure to solve moderate-to-severe knee osteoarthritis and has a high success rate. It mainly relaxes the soft tissue and bone tissue of the knee joint through the balance of the joint space, corrects the mechanical axis of the lower limbs, rebuilds the joint stability, relieves the symptoms of the patient, reduces the time in bed, achieves normal early activities, and restores the knee limbs [ 1 ]. Biomechanical analysis shows that correct alignment of prosthetic components is one of the most critical features of successful hip and knee replacement, and the key is accurate intraoperative amputation.…”
Section: Introductionmentioning
confidence: 99%
“…Hip and knee replacement is a procedure to solve moderate-to-severe knee osteoarthritis and has a high success rate. It mainly relaxes the soft tissue and bone tissue of the knee joint through the balance of the joint space, corrects the mechanical axis of the lower limbs, rebuilds the joint stability, relieves the symptoms of the patient, reduces the time in bed, achieves normal early activities, and restores the knee limbs [ 1 ]. Biomechanical analysis shows that correct alignment of prosthetic components is one of the most critical features of successful hip and knee replacement, and the key is accurate intraoperative amputation.…”
Section: Introductionmentioning
confidence: 99%
“…SNL was not detected in the zones inferior to the saphenofemoral junction nor was there drainage directly into the pelvis ( 18 ). Another study of this combined technology showed SPECT/CT to have a high sensitivity and specificity of 88.8% and 86.7%, respectively ( 36 ).…”
Section: Sln Biopsymentioning
confidence: 99%